Can the war on Iraq bring democracy to the Middle East? - Bouchaib Silm. (2008)
The war on Iraq was based on insufficient documents that failed to provide legitimization to the war, and also sought to criminalize Saddam's regime. As a result, the idea of a democratic Middle East is facing criticism. This study will also show that such projects are both uncertain and vital.